Step-by-step explanation:
-2x+3=x+12
combin like terms
-2x-x=12-3
-3x=9
x=9/-3
x=-3
Answer:
5x^2-18x -8
Step-by-step explanation:
Answer is A
The binomial can be factored using the difference of squares formula a2-b2 = (a+b) (a-b) where a=x and b=9
(X+9) x(x-9)
When 1 is added to another 1 they join together to form a 2. Bruh idk what 1+1 long method is. But I hope it helped.
All of them seem pretty correct.
Also the answer to 12 is this...
Remove unnecessary parentheses
-6x2/3p^8x3
Then reduce the #’s with the greatest common divisor 3
-6x2p^8
Calculate the product
-12p^8
And that’s your answer:)))